UJI FRAKSI DAUN SEMBUNG (Blumea balsamifera (L.) Dc) TERHADAP PENURUNAN KADAR GLUKOSA DARAH MENCIT (Mus musculus) - Yeni Agustin; Mayaranti Wilsya; Dila Natalia (Yayasan Nusantara Hasana Berdikari, 2026)
Diabetes Mellitus is a metabolic disorder characterized by elevated blood glucose levels due to absolute or relative insulin deficiency. The Sembung plant (Blumea balsamifera (L.) Dc) is a medicinal plant traditionally used to help lower blood glucose levels. This study aimed to determine the effectiveness of sembung leaf fractions in reducing blood glucose levels in sucrose-induced mice. This research used a pre- and post-test control group design to compare blood glucose reduction between mice given a 4.2% concentration of Sembung leaf fractions and a positive control group treated with glibenclamide. The results showed that oral administration of Sembung leaf fractions at a 4.2% concentration reduced blood glucose levels at 120 minutes, with average results as follows: n-hexane fraction as 117.5 mg/dL, ethyl acetate fraction at 132.8 mg/dL, and water fraction at 113.5 mg/dL.The n-hexane fraction, ethyl acetate fraction, and water fraction of Sembung leaves were effective in reducing blood glucose levels in mice. Among them, the water fraction showed the greatest effect.